2012
DOI: 10.1590/s0100-736x2012000800004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of virulence factors in Aeromonas hydrophila obtained from fish

Abstract: Pesq. Vet. Bras. 32(8) Multiple factors can be involved in the virulence processes of Aeromonas hydrophila. The objective of the present paper was to verify the presence of aerolysin, hidrolipase, elastase and lipase virulence genes through the polymerase chain reaction (PCR) in A. hydrophila isolates obtained from ϐish of the São Francisco River Valley, and to evaluate virulence according to the presence of these genes in Nile tilapia ϐingerlings. One hundred and fourteen isolates from the bacteria were used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
36
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 33 publications
7
36
0
4
Order By: Relevance
“…This has been shown previously in A. hydrophila isolated from fish hosts other than mullet (Oliveira et al . ; Abd‐El‐Malek ), suggesting a general feature for this bacterium. Our study showed that none of the isolates harboured all the studied virulence genes (Table ).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…This has been shown previously in A. hydrophila isolated from fish hosts other than mullet (Oliveira et al . ; Abd‐El‐Malek ), suggesting a general feature for this bacterium. Our study showed that none of the isolates harboured all the studied virulence genes (Table ).…”
Section: Discussionmentioning
confidence: 88%
“…; Oliveira et al . ; Furmanek‐Blaszk ). Indeed, aerA gene has been also identified in non‐ A. hydrophila spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the characterization of bacteria and their virulence factors, polymerase chain reaction (PCR) and gene sequencing are widely used in the field of aquatic science (Rahman et al, ). The detection and analysis of virulence factors play an important role in the study of pathogenicity of any pathogen, as these factors act in a coordinated manner in disease progression (Foysal, Rahman, & Prodhan, ; Oliveira, Gouveia, & Costa, ). Homology modelling is another common method for the analysis of protein structure and function on the basis of closest homolog or template.…”
Section: Introductionmentioning
confidence: 99%